Cissampelos sympodialis Eichl (Menispermaceae) leaf extract induces interleukin-10-dependent inhibition of Trypanosoma cruzi killing by macrophages - Alexandre-Moreira,M.S. (2003)
The aqueous fraction of the ethanolic extract (AFL) of Cissampelos sympodialis Eichl (Menispermaceae), popularly known as milona, has been shown to have both immunosuppressive and anti-inflammatory effects. In the present study we investigated the modulation of macrophage antimicrobicidal activity by in vitro treatment with the extract from C. sympodialis. Normal and thioglycolate-elicited mouse peritoneal macrophages were infected in vitro with the protozoan Trypanosoma cruzi DM28c clone. We observed that the AFL (used at doses ranging from 13 to 100 µg/ml) increased T. cruzi growth and induced a 75% reduction in nitric oxide production. This inhibition could be mediated by the stimulation of macrophage interleukin-10 (IL-10) secretion since the in vitro treatment with the AFL stimulated IL-10 production by T. cruzi-infected macrophages. These results suggest that the anti-inflammatory effect of the AFL from C. sympodialis could be, at least in part, mediated by the inhibition of macrophage functions and that the inhibition of macrophage microbicidal activity induced by the C. sympodialis extract may be mediated by the decrease in macrophage function mediated by interleukin-10 production.